Affirming Aboriginal identities: art production in central Queensland. (3rd April 2021) - Fredericks, Bronwyn; Bradfield, Abraham
ABSTRACT: Alongside Toonooba (the Fitzroy River) in central Queensland, Australia, a series of flood markers are embedded within the earth, commanding attention to the river that flows on one side and the colonial infrastructure of Rockhampton on the other. Honouring Land Connections is an artwork that asserts Indigenous voices, marks Indigenous spaces, and encourages visitors to engage in conversation with Indigenous culture and art. This paper considers Indigenous art as a form of social action. Firstly, it discusses the value of such art projects, and presents an Indigenous perspective of their meaning, addresses their role in creating and embodying culture and identity, how they express and share culture, along with collaborative approaches, and the importance of learning on and from Country. It concludes with a discussion of the political and cultural meaning created through art, suggesting that it is impossible for a public artwork like Honouring Land Connections to not be political. This article explores how art facilitates an interactive social space through which Aboriginal artists affirm, negotiate and share their identities while challenging preconceptions of place and identities reminding us that Aboriginal presence outlasts the moment of its production and imprints itself on the landscape and people's consciousness.